América Latina: urbanização e luta pelo direito à cidade - Balestrini, Millton (Universidade Federal de São Carlos, 2022)
Several efforts were concerned about indicating paths and opportunities for the development of Latin America. As for example, the ECLAC in the 1950s and the organization of the Mercosur, in 1991. However, the continent as a whole was never able to face its structural issues. The necessary break with the hegemony of a model based on exporting commodities, defining plans for a coordinated industrialization supported by public economic policies, and investments in education and training of specialized labour, for instance, are all facts that never occurred on a sufficient scale to configure a strong development process. Issues that limit economic growth, such as chronic poverty and deep regional social inequalities, were not overcome by attempts at industrialization. The structural deficiencies of the development model, still based today on the production and export of commodities produced on large estates, which perpetuates the great imbalances on the continent, making the land issue a cross-cutting factor in the historical development of the countryside and Latin American cities. The exodus from the countryside and the rapid process of urbanization on the continent, contrary to popular belief, has little to do with the years of our industrialization processes; the high rates of urbanization are understood from the point of view of conflicts and disputes over land, first as a means of production, and then as an instrument of speculation, but always as a sign of wealth and power. The urban and social consequences of this unequal struggle are better understood and made explicit in the precariousness of the outskirts of our cities, where the poor are hidden from the eyes of the world and local elites. However, this context of segregation can lead to the emergence of cultural expressions, relevant voices, as well as powerful organized popular movements, in the struggle for the right to have rights.
Latin America: urbanization and the fight for the right to the city
Keywords: Pobreza; Terras; América Latina; Direito à cidade; Urbanização; Poverty; Land property; Latin America; Urbanization; Right to the city; Tierras; Urbanización; Derecho a la ciudad; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::FUNDAMENTOS DE ARQUITETURA E URBANISMO; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::HISTORIA; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO